Synthesisand Characterization of Benzothiophene‐3‐carbonitrile Derivative and Its Interactions with Human Serum Albumin (HSA). Issue 41 (4th November 2019) - Parveen, Mehtab; Aslam, Afroz; Alam, Mahboob; Siddiqui, Mohd Faizan; Bano, Bilqees; Azaz, Shaista; Silva, Manuela Ramos; Silva, P. S. Pereira
Abstract: A series of biologically active compounds, i. e ., benzothiophene‐3‐carbonitrile derivatives, were synthesized from 1, 3‐cyclohexanediones and malononitrile in the presence of base using the well‐known Gewald reaction. This recyclable approach resulted in significant improvement in overall yield (85‐90%), high purity and minimized production of chemical waste without using toxic reagents. The formation of compound, 2‐amino‐7‐oxo‐4, 5, 6, 7‐tetrahydro‐1‐benzothiophene‐3‐carbonitrile (3 a ) was additionally supported by X ‐ray crystallography and was found to crystallize in P 21 /n space group. The mode of binding of 3 a with human serum albumin (HSA) was studied by FTIR, UV spectroscopy, fluorescence spectroscopy, circular dichroism (CD) and molecular docking studies. The fluorescence results establish that compound 3 a interacted with HSA via static quenching mechanism with a binding affinity of 11.49 × 10 −4  mol −1 and Gibbs free energy change (ΔG) of−6.8 kcal mol −1 . Molecular docking has been used to calculate the probable mode of interaction of compound 3 a with HSA. Abstract : In extension of our research on biologically active sulphur based heterocycles we herein report the synthesis of fused heterocyclic systems, consolidating benzothiophene moiety via the reaction of 1, 3‐cyclohexanedione derivative 1 (a–c) with malononitrile and sulphur by utilizing conventional procedures with its spectral characterizations like FTIR, NMR and Mass. The synthesized compound 3 a was tested for HSA activity which was further demonstrated by molecular docking study.